2016
DOI: 10.1016/j.psychres.2016.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk characteristics among aborted, interrupted, and actual suicide attempters

Abstract: Few studies have investigated suicide risk characteristics associated with interrupted and aborted suicide attempts. The present study aimed to empirically examine whether assessing a history of interrupted and aborted suicide attempts is valuable when assessing suicide risk, given the relative lack of literature in this area to date. To inform this question, the current study examined differences in risk factors for suicidal behavior among individuals who have carried out a suicide attempt, individuals who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
1
16
1
4
Order By: Relevance
“…Thus, aborted attempts and interrupted attempts performed differently than actual attempts. This differs somewhat from a prior study in which few meaningful differences were reported in individuals on the basis of whether they had aborted, interrupted, or actual SAs (Burke, Hamilton, Ammerman, Stange, & Alloy, 2016). However, the prior study was cross‐sectional and in undergraduates, perhaps accounting for the different findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, aborted attempts and interrupted attempts performed differently than actual attempts. This differs somewhat from a prior study in which few meaningful differences were reported in individuals on the basis of whether they had aborted, interrupted, or actual SAs (Burke, Hamilton, Ammerman, Stange, & Alloy, 2016). However, the prior study was cross‐sectional and in undergraduates, perhaps accounting for the different findings.…”
Section: Discussioncontrasting
confidence: 99%
“…A history of (or active) NSSI also places a person at higher risk . A higher risk for suicide was associated with a higher number of methods used, a higher amount of NSSI performed, and more frequent NSSI performed .…”
Section: Resultsmentioning
confidence: 95%
“…Another important factor that increases an individual's risk of suicidal requiring assessment is NSSI. Clinicians should take a detailed history regarding the frequency and number of methods, as higher numbers of each increase risk for suicide .…”
Section: Resultsmentioning
confidence: 99%
“…For example, a positive response to a single item could include aborted or interrupted attempts in addition to suicide attempts. However, recent work suggests there may be few differences between those with a history of suicide attempt versus interrupted/aborted attempts only (Burke, Hamilton, Ammerman, Stange, & Alloy, 2016), somewhat mitigating these concerns. An additional limitation of the single item measure is that it cannot provide information about the intent, lethality, recency, or frequency of suicide attempts—characteristics that may relate to response to threat.…”
Section: Discussionmentioning
confidence: 99%